Biomechanical Analysis of Lifting Dumbbell and Jumping Movements Using Kinovea Application - Lawi, Ansarullah; Jessica, Rye; Fadilla, Wilda (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2024)
This study delves into the biomechanics of lifting dumbbell and jumping movements, pivotal exercises in resistance training and fundamental for various activities, employing the Kinovea application. Twenty male and female participants from Institut Teknologi Batam's Industrial Engineering study program underwent protocols recorded by a Sony HDR-CX405 camera. Kinematic analysis measured parameters using the Kinovea application, revealing participants' mean age, height, and weight. Dumbbell lifting entailed a mean distance of 0.45 ± 0.05 m and joint angles at shoulder (157.50 ± 5.77°), elbow (146.25 ± 6.25°), and wrist (45.00 ± 5.77°). Jumping achieved a mean height of 35.50 ± 2.87 cm, with joint angles at ankle (25.00 ± 5.77°), knee (90.00 ± 5.77°), and hip (120.00 ± 5.77°). Findings aligned with previous studies, emphasizing joint angles' importance. Implications include exploring muscle activation patterns and metabolic demands for future research and informing tailored training programs to enhance lifting and jumping abilities, offering valuable insights into biomechanics for sports and exercise training applications.